1985
DOI: 10.2135/cropsci1985.0011183x002500010002x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cultivar, Environment, and Their Interaction and Stability Analyses on Milling and Baking Quality of Soft Red Winter Wheat1

Abstract: The effect of cultivar, environment, and their interactions on soft red winter wheat (Triticum aestivum L.) quality has never been determinated in the southeastern United States. In this study, 22 soft wheat cultivars and 2 hard wheat cultivars were grown in 12 southeastern environments in a randomized complete block design having two replications. Flour yield, whole grain protein percent, particle size index, and alkaline water retention capacity were measured. Highly significant differences were detected amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 0 publications
7
59
1
Order By: Relevance
“…This was likely due to the relatively limited environmental effect arising from the use of only three Manitoba growing sites over 2 yr. As well, eight genetically diverse genotypes were used in the Lukow and McVetty (1991) study, thus promoting the genotype effects. Several other genotype × environment studies on wheat quality have shown similar results to ours with the relative magnitude of the genotype × environment interaction effect being considerably smaller than either genotype or environment (Busch et al 1969;McGuire and McNeal 1974;Fowler and De La Roche 1975;Baker and Kosmolak 1977;Baenziger et al 1985;Lukow and McVetty 1991;Peterson et al 1992;Ames et al 1999;Mikhaylenko et al 2000;Preston et al 2001).…”
Section: Relative Influence Of Genotype Environment and G × × E Intesupporting
confidence: 87%
See 1 more Smart Citation
“…This was likely due to the relatively limited environmental effect arising from the use of only three Manitoba growing sites over 2 yr. As well, eight genetically diverse genotypes were used in the Lukow and McVetty (1991) study, thus promoting the genotype effects. Several other genotype × environment studies on wheat quality have shown similar results to ours with the relative magnitude of the genotype × environment interaction effect being considerably smaller than either genotype or environment (Busch et al 1969;McGuire and McNeal 1974;Fowler and De La Roche 1975;Baker and Kosmolak 1977;Baenziger et al 1985;Lukow and McVetty 1991;Peterson et al 1992;Ames et al 1999;Mikhaylenko et al 2000;Preston et al 2001).…”
Section: Relative Influence Of Genotype Environment and G × × E Intesupporting
confidence: 87%
“…Wheat kernel development and biomolecule accumulation are strongly influenced by genotype and environmental parameters (Baenziger et al 1985;Peterson et al 1992). Environmental parameters such as useful-heat accumulation, higher than optimal temperature, and water stress are predominant factors influencing grain development.…”
mentioning
confidence: 99%
“…Similarly, many other studies demonstrated that environmental conditions have a larger effect on protein content than the genotype (e.g. Baenziger et al, 1985;Uhlen et al, 1998;Rharrabti et al, 2001;Mut et al, 2010). Protein quality, measured by alveograph W parameter, appeared to be influenced in a similar degree by genotype and environment.…”
Section: Discussionmentioning
confidence: 68%
“…Several other authors (Baenziger et al 1985, Robert and Denis 1996, Peterson et al 1998) also obtained low G × E component for quality traits.…”
Section: Effect Of Genotype Environment and Their Interaction To Thementioning
confidence: 83%